2008
DOI: 10.1080/02656730802253117
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia on mesenchymal stem cells (MSCs) can sensitize tumor cells to undergo cell death

Abstract: Hyperthermia, the procedure of raising the temperature of tumor-loaded tissue to 40 degrees -43 degrees C, has been applied to various established cancer treatments. Although the mechanism of hyperthermia in cancer treatment is well-known, there are few or no studies regarding the effect of hyperthermia on the tumor-supportive stroma. Mesenchymal stem cells (MSCs) display the potential for differentiation into various tissues. MSCs are also reported to play a role as potential precursors for tumor stroma in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 33 publications
1
24
0
1
Order By: Relevance
“…The cytotoxic effects of hyperthermia have been associated with necrotic cell death [25], induction of apoptosis [26], protein unfolding and subsequent protein aggregation [27], compromised plasma membrane [28,29] and nuclear matrix structure [30], DNA double strand breaks [31], DNA repair mechanism inhibition [32,33] and cell cycle arrest [34]. In the present study we have shown that exposing both colon cancer cell lines to increasing TD decreases cell viability.…”
Section: Discussionmentioning
confidence: 94%
“…The cytotoxic effects of hyperthermia have been associated with necrotic cell death [25], induction of apoptosis [26], protein unfolding and subsequent protein aggregation [27], compromised plasma membrane [28,29] and nuclear matrix structure [30], DNA double strand breaks [31], DNA repair mechanism inhibition [32,33] and cell cycle arrest [34]. In the present study we have shown that exposing both colon cancer cell lines to increasing TD decreases cell viability.…”
Section: Discussionmentioning
confidence: 94%
“…A study demonstrated that migration of MSCs was promoted by exposure to tumor cell-conditioned medium, thus causing an increase in production of stromal cell-derived factor (SDF)-1 protein [41]; another study showed that MSCs within the tumor stroma promoted breast cancer metastasis by CCL5/CCR5 signaling [18]. Our previous studies demonstrated that cytokines secreted by MSCs can influence tumor cell growth [42,43]. Therefore, manipulation of the interaction between MSCs within the tumor stroma and tumor cells might improve conventional cancer therapy.…”
Section: Discussionmentioning
confidence: 97%
“…More importantly, a study was carried out showing that MSCs within the tumor stroma promote breast cancer metastasis by CCL5 signaling through the chemokine receptor CCR5 expressed in the tumors (18). Our previous studies demonstrated that cytokines secreted by MSCs can influence tumor cell growth (43,44). Therefore, manipulation of the interaction between MSCs within the tumor stroma and tumor cells might improve conventional cancer therapy.…”
Section: Discussionmentioning
confidence: 99%